A galactose‐specific sugar: phosphotransferase permease is prevalent in the non‐core genome of Streptococcus mutans. (20th February 2013) - Zeng, L.; Xue, P.; Stanhope, M.J.; Burne, R.A.
Summary Three genes predicted to encode the A, B and C domains of a sugar : phosphotransferase system (PTS) permease specific for galactose\(EIIGal) were identified in the genomes of 35 of 57 recently sequenced isolates of Streptococcus mutans, the primary etiological agent of human dental caries. Mutants defective in the EIIGal complex were constructed in six of the isolates and showed markedly reduced growth rates on galactose‐based medium relative to the parental strains. An EIIGal‐deficient strain constructed using the invasive serotype f strain OMZ175 (OMZ/IIGal) expressed significantly lower PTS activity when galactose was present as the substrate. Galactose was shown to be an effective inducer of catabolite repression in OMZ175, but not in the EIIGal‐deficient strain. In a mixed‐species competition assay with galactose as the sole carbohydrate source, OMZ/IIGal was less effective than the parental strain at competing with the oral commensal bacterium Streptococcus gordonii, which has a high‐affinity galactose transporter. Hence, a significant proportion of S. mutans strains encode a galactose PTS permease that could enhance the ability of these isolates to compete more effectively with commensal streptococci for galactose in salivary constituents and the diet.